An automated assay to measure phagocytosis of Cryptococcus neoformans - Chang, Andrew L (Curr Protoc Microbiol, 2019)
Cryptococcus neoformans is an opportunistic fungal pathogen, which causes meningoencephalitis that kills 200,000 individuals worldwide each year. It is ubiquitous in the environment and is first inhaled into the lungs of the host, where it is taken up by phagocytes. The interaction of these fungal cells with host phagocytes, therefore, is a critical step in the pathogenesis of this disease. One characteristic of this initial step in host:pathogen interactions is the avidity with which fungal cells are taken up by phagocytes, described by the phagocytic index. In this chapter, we detail a high-throughput method of directly assessing the phagocytic index of fungal cells using an imaging-based paradigm. By automating image collection and processing, this method permits rapid assessment of this critical host interaction.